Convective heat transfer of ferrofluid in a lid-driven cavity with a heat-conducting solid backward step under the effect of a variable magnetic field - Gibanov, Nikita S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Nusier, Osama K. (Taylor & Francis Inc, 2017)
The effect of variable magnetic field on the mixed convective flow of a ferrofluid within a lid-driven cavity has been analyzed numerically. A heat-conducting solid block is located in the bottom part of the cavity. Governing partial differential equations have been formulated taking into account that the magnetic source is a point source located over the moving lid. Analysis has been performed for a wide range of Hartmann number, nanoparticles volume fraction, and magnetic number. It has been found that the growth of the magnetic number leads to the heat transfer enhancement.
Keywords: Mhd Mixed Convection; Natural-Convection; Square Cavity; Fe3O4-Water Nanofluid; Numerical-Simulation; Entropy Generation; Enclosure; Radiation; Flow